PENDAMPINGAN UMKM DESA MUARA KECAMATAN WANASALAM MELALUI STRATEGI PEMASARAN ONLINE UNTUK KELOMPOK USAHA BERSAMA KARYA MANDIRI - Basuki Rakhim S P; Oni Syahroni; Tazkia Kalda P; Vita Maulana; Maulana Yusuf; Uswatun Hasanah (JIPAM : Jurnal Ilmiah Pengabdian kepada Masyarakat, 2022)
The purpose this study to determine the marketing strategies carried out by MSME actors, especially in the city of South Tangerang. One of the marketing strategies is through E-commerce. E-commerce is the process of buying and selling products electronically. E-Commerce itself has grown in recent years and is slowly replacing traditional shops. The data analysis method used in this research is descriptive qualitative, namely descriptive does not provide treatment, manipulation or modifying the variables studied, but describes a condition as it is. The only treatment given is the research itself, which is carried out through observation, interviews, and documentation. The results showed that MSMEs, especially in the city of South Tangerang, use marketing strategies through E-commerce. So, that their product sales and skills can increase